Implementation Of Teacher Role-Modeling-Based Habituation Activities In Developing Discipline Among 5–6-Year-Old Children In Group B At RA Al Fikri Sukanagara - Hera Siti Nurjanah; Eva Manfaatin Kartadinata; Ika Rustika Zainah (FKIP UNSULTRA, 2026)
Discipline in early childhood needs to be formed through concrete examples, repeated routines, and consistent guidance from teachers. This study aims to describe the implementation of habituation activities based on teacher exemplary behavior in shaping the discipline of children aged 5-6 years in Group B at Raudhatul Athfal Al Fikri Sukanagara. This study used a descriptive qualitative method. The research subjects consisted of the principal, one Group B teacher, and children aged 5-6 years. Data were collected through observation, interviews, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing, while data validity was strengthened through source and technique triangulation. The findings show that discipline was developed through daily routines, such as arriving on time, greeting, lining up, praying, following classroom rules, waiting for turns, tidying up learning tools, maintaining cleanliness, and completing activities according to teacher instructions. Teacher exemplary behavior appeared through punctuality, polite speech, readiness to teach, neatness, and consistency in applying classroom rules. The study also found that children showed different responses because of differences in character, home habits, and self-control. This study concludes that teacher exemplary behavior is an important basis for habituation activities because children understand discipline more easily through actions they see, experience, and repeat every day.